(untitled) (Práxis Educativa, 2025)
The responsibility for teacher education in Higher Education legally lies with stricto sensu graduate programs. However, there are no national guidelines on how such training should be conducted. It is worth noting that the Teaching Internship (Estágio de Docência – ED), implemented by the Coordination for the Improvement of Higher Education Personnel (CAPES), is an action intentionally aimed at teacher education. Therefore, this study, based on documentary research, investigated how teacher education in Higher Education is being carried out for graduate students, considering the scope of the ED along with other formative actions, such as the offering of courses in Graduate Programs in the fields of Education and Chemistry. Different scenarios of ED development were identified, with few examples of institutional regulation. This reality highlights the need for further studies on the extent of ED institutionalization, as well as on the role of CAPES as the agency responsible for the regulation and performance evaluation of Graduate Programs. Keywords: Higher Education Teaching. Teaching Internship. CAPES.